Comparison of HER2 status by fluorescence in situ hybridisation and immunohistochemistry in gastric cancer - Chen, Ming; Li, Yan; Ming, Zhou; Biao, Ai (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study: To investigate the differences and relevance, and to evaluate the clinical significance of fluorescence in situ hybridisation and immunohistochemistry (IHC) in detecting HER2 in gastric cancer tissues. Material and methods: The expression of HER2 protein and the amplification of the HER2 gene in 118 gastric cancer tissues were detected by immunohistochemistry and fluorescence in situ hybridisation, respectively. Results : Using IHC, we found that in 40 cases (33.9%) the HER2 expression was at level 0, in 33 cases (28.0%) the HER2 expression was at level 1+, in 16 cases (14%) the HER2 expression was at level 2+, and in 29 cases (25.6%) the HER2 expression was at level 3+, respectively. Using the FISH test, 38 of 118 cases (32.2%) were judged as positive results. The concordance rate between the results of IHC and FISH in all cases was 85.6%. The concordance rate of IHC and FISH was high in cases of HER2 expression at level 0, 1+ and 3+ according to IHC, but low in cases of 2+ according to IHC (43.8%). Conclusions: Immunohistochemistry cannot predict HER2 gene amplification accurately. The FISH test should be executed in IHC 2+ cases.